2012
DOI: 10.3346/jkms.2012.27.10.1196
|View full text |Cite
|
Sign up to set email alerts
|

Association between Total Bilirubin and Hemoglobin A1c in Korean Type 2 Diabetic Patients

Abstract: Recent studies have shown that bilirubin is negatively associated with hemoglobin A1c (HbA1c) in the general population. The association between bilirubin and HbA1c in serum of diabetes patients has not yet been studied. The aim of the present study was to evaluate the association between total bilirubin and HbA1c in Korean patients with type 2 diabetes. A total of 690 of the 1,275 type 2 diabetes patients registered with the public health centers in Seo-gu, Gwangju and Gokseong-gun, Jeollanam-do participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
7
21
0
2
Order By: Relevance
“…This finding is consistent with previous studies (33,34) reporting inverse associations between total bilirubin levels and HbA 1c values, independent of other risk factors. Bilirubin, which results from heme catabolism, has antioxidant properties, and higher levels have been associated with a decreased risk of carotid atherosclerosis, coronary artery disease, and cerebrovascular disease (3537).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies (33,34) reporting inverse associations between total bilirubin levels and HbA 1c values, independent of other risk factors. Bilirubin, which results from heme catabolism, has antioxidant properties, and higher levels have been associated with a decreased risk of carotid atherosclerosis, coronary artery disease, and cerebrovascular disease (3537).…”
Section: Discussionsupporting
confidence: 93%
“…However, a study from Choi SW et al evaluated the relationship between HbA1c and bilirubin in 690 patients with type 2 diabetes mellitus and found that bilirubin concentrations were negatively associated with HbA1c, independent of gender, age, and other confounding factors [19]. Because several studies have confirmed that high bilirubin concentrations are inversely associated with insulin resistance [2022], T1DM is possibly due to β-cell destruction and leads to absolute insulin deficiency rather than insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, smokers had a greater risk of amputation than non-smokers, and women had a lower risk than men [1]. Furthermore, there is also an effect of glycaemia on bilirubin levels [1]; for example, others have reported that higher HbA 1c levels were associated with lower bilirubin levels in patients with type 2 diabetes [3]. This association is of interest because the amputation group had higher HbA 1c levels than those who did not need an amputation during the FIELD trial [1].…”
Section: Fieldmentioning
confidence: 99%